REALISM/ANTIREALISM DEBATE: A SELECTION OF THE MOST IMPORTANT ARGUMENTS OF THE DEBATE - RUSU, Horea (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
Realism/Antirealism Debate: A Selection of the Most Important Arguments of the Debate. The present article intends to explore features of the realism/antirealism dispute. The intention is to offer arguments in favor of both sides for a better understanding of the debate. The article wants to use both logical arguments and sociological or psychological ones.